The Tower of Pisa - Burland, J. B., author.
1 online resource (vii, 54 pages)
Keywords: "The Leaning Tower of Pisa is known worldwide for its five-degree lean. The Tower is the Campanile of the Cathedral, which together with the Baptistry and Cemetery form a breath-taking collection of monuments which are regarded as supreme examples of early Renaissance Romanesque architecture. In March 1990 the Tower was closed to the public as it was declared unsafe and close to collapse. A Commission was set up by the Italian Government with the task of developing and implementing stabilisation measures. This book begins with a brief description of the history of the Tower and its construction. The reader is then introduced to the huge challenges faced by the Commission in designing and implementing appropriate stabilisation measures whilst at the same time satisfying the demanding requirements of conserving a world heritage monument. In particular, two historical studies are described which proved to be most valuable in arriving at suitable stabilisation measures. The first was a deduction of the history of inclination of the tower during and subsequent to construction. The results of this study were used to calibrate a sophisticated numerical model of the tower and the underlying very soft ground which proved vital in evaluating the effectiveness of various stabilisation schemes. The second study was of measurements of movement made since 1911. This latter study revealed an unexpected mechanism of foundation movement which proved crucial in developing the temporary and permanent stabilisation measures and which resulted in the Tower being re-opened to the public in June 2001. The book will appeal to both professionals and students in the fields of Architecture and Civil Engineering. It will also interest specialised audiences of geotechnical engineers and conservation architects. It may also be of wider interest to anyone planning to visit Pisa or who is intrigued as to what caused the Tower to lean and how it was stabilised"--